The Epigenetic Assessment of Human Spermatogenic Cells Derived from Obstructive Azoospermic Patients in Different Culture Systems - Zahiri, Maria; Movahedin, Mansoureh; Mowla, Seyed Javad; Noruzinia, Mehrdad; Koruji, Morteza; Nowroozi, Mohammad Reza; Bashiri, Zahra (Urology Journal, 2020)
Purpose: Generating functional gametes for patients with male infertility is of great interest. We investigated different cultural systems for proliferation of SSCs derived from obstructive azoospermic patients. Materials and Methods: Testicular cells were obtained from men with obstructive azoospermia. After enzymatic digestion process, cells were assigned to various groups: culture of SSCs in the dish without cover (control group), co-culture of SSCs with infertile Sertoli cells (I), co-culture of SSCs with fertile Sertoli cells (II), culture of SSCs on nanofiber (covered with laminin) (III), culture of testicular cell suspension (IV). Then cells were cultured and colony formation, gene-specific methylation (by MSP), quantitative genes expression of pluripotency (Nanog, C-Myc, Oct-4) and specific germ cell (Integrin α6, Integrin β1, PLZF) genes were evaluated in five different culture systems. Results: Our findings indicate a significant increase in the number and diameter of colonies in IV group in compare to control group and other groups. Expression of germ specific genes in IV group were significantly increased (P ≤ 0.05) and levels of expression of pluripotency genes were significantly decreased in this group (P ≤ 0.05) compared with other groups. Gene-specific pattern of methylation of examined genes showed no changes in culture systems during the culture era. Conclusion: A microenvironment capable of controlling the proliferation of cell colonies can be restored by testicular cell suspension.